USING PORTFOLIO AS A SOURCE OF INFORMATION ABOUT LEARNING PROCESS - Andhini, Rifa; Halimi, Sisilia Setiawati, Dr. (International Review of Humanities Studies, 2021)
Alternative assessments are said to be suitable for young language learners, but are rarely used by language teachers from all educational levels. One of the causes is teachers’ lack of knowledge regarding the best ways to utilize alternative assessments. This research explores how an English teacher for young learners can use portfolio, an alternative assessment, as a source of information about learning process. Data from journal entries and stimulated recall sessions that focus on the participant’s lesson plans were collected every week to reveal how portfolio was used, while initial and final interviews were done to reveal the participant’s perception about portfolio. The results indicate that portfolio could help the participant identify learners’ weaknesses, strengths and needs as she started exploring a topic; determine the teaching focus, suitable teaching materials and appropriate teaching strategies; monitor learners’ development; and decide whether the topic needs to be explored further. The participant also has a positive perception about using portfolio. Some issues about portfolio, such as its use alongside other forms of assessment, are also revealed. The results provide new, more specific information about how teachers can use portfolio.